The Constructs of Seamless Blended Digital Learning Program from the Lenses of Faculty and Students of Laguna University: Towards A Sustainable Program - Fucio, Roel L.; Ardizone, Michael; Domingo, Olga J.; Maningas, Zandra N. (International Journal of Computing Sciences Research, 2023)
Purpose – The study (re)constructed views of faculty and students on Seamless Blended Digital Learning Program of Laguna University vis-à-vis its impact on Teaching and Learning; Achievement of learning outcomes; Assessment; Synergy between and among faculty and students; and Acquisition of soft skills. Method – This research is designed to explore modular distance learning as contemporary teaching strategy, but specifically, it will address the instructors and learners’ perceptions enclose to their teaching and learning experiences under the new normal education settings. This research will be purely qualitative in its methods of data collection and analysis.  Results – It was assumed that the faculty members and students, both psychologically unprepared on drastic educational change, view Seamless Blended Digital Learning Program of Laguna University, similarly, based on their background and teaching/learning conditions at home. Conclusion – SBDLP is a changed in the educational system, which must be accepted, embraced, and lived by the University. Both faculty members and students noted time as one of the major demands of the new learning platform; and accepted the need to adjust technologically and academically with the implementation and possible continuation of SBDLP. Recommendations – For the students, a seminar/webinar on independent learning or distance learning should be prepared for the students to avoid dropouts or Leave of Absence in the midst of pandemic.  For the faculty they should take a more active role in the learning and training process. They can invite and encourage team members to help in shaping the modules for the courses. Research Implications – A benchmarking study of the construct of SBDLP among schools having a learning management system, variables like satisfaction and academic performance can be considered.